2020
DOI: 10.3390/genes11030268
|View full text |Cite
|
Sign up to set email alerts
|

Shared Molecular Genetic Mechanisms Underlie Endometriosis and Migraine Comorbidity

Abstract: Observational epidemiological studies indicate that endometriosis and migraine co-occur within individuals more than expected by chance. However, the aetiology and biological mechanisms underlying their comorbidity remain unknown. Here we examined the relationship between endometriosis and migraine using genome-wide association study (GWAS) data. Single nucleotide polymorphism (SNP) effect concordance analysis found a significant concordance of SNP risk effects across endometriosis and migraine GWAS. Linkage d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 87 publications
4
70
0
2
Order By: Relevance
“…The biological mechanisms underlying this comorbidity remain unknown. Interestingly, a recent genome-wide association study found a positive and highly significant genetic correlation ( p = 2.30 × 10 −25 ) between endometriosis and migraine and suggested a role for genes involved in interleukin-1 receptor binding, focal adhesion-PI3K-Akt-mTOR-signaling, mitogen-activated protein kinase (MAPK), and tumor necrosis factor-alpha (TNF-α) signaling in the association between these two traits (Adewuyi et al, 2020 ).…”
Section: Metabolic and Endocrine Comorbidities Of Migrainementioning
confidence: 99%
See 1 more Smart Citation
“…The biological mechanisms underlying this comorbidity remain unknown. Interestingly, a recent genome-wide association study found a positive and highly significant genetic correlation ( p = 2.30 × 10 −25 ) between endometriosis and migraine and suggested a role for genes involved in interleukin-1 receptor binding, focal adhesion-PI3K-Akt-mTOR-signaling, mitogen-activated protein kinase (MAPK), and tumor necrosis factor-alpha (TNF-α) signaling in the association between these two traits (Adewuyi et al, 2020 ).…”
Section: Metabolic and Endocrine Comorbidities Of Migrainementioning
confidence: 99%
“…Investigations of metaboloendocrine comorbidities of migraine further support the role of shared molecular genetic mechanisms between all these highly prevalent medical conditions. Migraine and diabetes, obesity, and endometriosis are complex genetic traits sharing common genes as well as common metabolic pathways (McCarthy et al, 2001 ; Netzer et al, 2008 ; Adewuyi et al, 2020 ). Further investigating these pathways will allow us to disentangle the biochemical mechanisms of migraine.…”
Section: Metabolic and Endocrine Comorbidities Of Migrainementioning
confidence: 99%
“…Interesting significant gene-wide associations also included FHL5 , a gene previously associated with migraine 47,48 , spatial memory 49 , and cerebral blood flow 50 , and SMYD3 , which previously came up in GWASs of cognitive ability 51,52 , suicide attempt 53 , and bipolar disorder 54 . However, the genes retrieved by our gene-wide analyses were not all related to traits exclusively relevant to the brain, but also to cardiovascular 55,56 , metabolic 57,58 , and drug response traits 59,60 .…”
Section: Discussionmentioning
confidence: 99%
“…Мигрень и эндометриоз являются генетически детерминированными заболеваниями, что подтверждено крупными полногеномными ассоциативными исследованиями [14][15][16]. Также предполагается, что важную роль в коморбидности мигрени и эндометриоза играет ген рецептора эстрогена 1 (ESR1), который отвечает за восприимчивость к мигрени и эндометриозу [17,18].…”
Section: сравнительный анализ болевого синдрома у пациенток с эндометunclassified